Beyond First Impressions: How Memorable Nature-Based Tourism Experience Fuels Revisit Intentions - Prianka, Winda Gafrilia; Arissaputra, Rivaldi; Yulianti, Siska Dewi (International Journal of Economics Development Research (IJEDR), 2024)
Nature tourism is rapidly growing in Indonesia, with West Java's natural beauty offering significant potential for the sector. Creating memorable tourism experiences is crucial for enhancing tourist satisfaction and encouraging revisit intentions. Despite the increasing interest, research specifically addressing how memorable nature-based tourism experiences affect revisit intentions in West Java is limited. Existing studies often overlook the unique aspects of memorable experiences in natural tourism contexts.This study aims to fill this gap by investigating the impact of memorable nature-based tourism experiences on revisit intentions in West Java. Employing a quantitative approach, data were collected from 233 tourists who had visited ecotourism sites in West Java at least twice. The analysis utilized Structural Equation Modeling (SEM) via SmartPLS to assess both measurement and structural models. The findings reveal that memorable nature-based tourism experiences significantly influence revisit intentions. Key factors contributing to memorable experiences include novelty, experiencescape, co-creation, intensification through social media, and overall satisfaction. These factors collectively enhance the likelihood of tourists returning to nature tourism destinations. The study's implications suggest that tourism operators in West Java should focus on creating and enhancing unique and engaging attractions, investing in high-quality services, and utilizing feedback systems to refine tourism offerings. Effective marketing strategies should emphasize the distinctive and memorable aspects of West Java's natural attractions to attract and retain tourists. This research contributes to the literature on nature tourism and provides practical insights for improving tourism strategies in West Java.